DINAMIKA STRUKTUR MODAL PERBANKAN - Nerissa Arviana; Ishak Ramli; Kurniati W Andini (Jurnal Kontemporer Akuntansi, 2023)
The purpose of this study was to determine whether taxes, credit, size of liquidity and bank profitability affect the bank's capital structure and whether the bank's capital structure affects the bank's liquidity and profitability. This study uses 93 samples, namely 31 banks listed on the Indonesian stock exchange in the 2018-2020 period. The results of this study indicate that taxes, firm size, liquidity and profitability affect the capital structure and capital structure affects liquidity and profitability